Online shopping: what make consumer’s prefer to it? / Wan Shahrul Aziah Wan Mahamad and Yong Azrina Ali Akbar - Wan Mahamad, Wan Shahrul Aziah; Ali Akbar, Yong Azrina (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Electronic Commerce has experienced a rapid growth in the last few decades and the advancement of Internet provides a prospect for online shopping and changed the way consumers buy goods and services (Anitha, 2017). With the ever-growing impact of the internet on the lifestyles of consumers, the internet has been becoming both a tool and a segment of cyberculture (Macek, 2004), and a more significant marketing medium.